Вплив білків AIMР1/p43 та EMAP II на клітини злоякісної пухлини - Kolomiiets, Mariia; Zayets, Volodymyr; Zaika, Leonid; Bolsunova, Olga; Kornelyuk, Oleksandr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):306